Teacher's Perception of Thermodynamic Law Module Developed in Training through Student’s Critical Thinking Skills - Risdianto, Eko; Fitria, Jeni; Johan, Henny; Macariola, Julie Simon (Journal of Social Work and Science Education, 2020)
This study determined teacher’s perceptions about the ability of modules developed in training students' critical thinking skills. This research is a part of research and development with the development model used, namely 3D Development, namely Define, Design, and Develop which was adapted. The instruments used were observation sheets, student needs questionnaire sheets and teacher perception questionnaire sheets. Questionnaire needs were given to 100 students of class XI Science while perception questionnaires were given to 30 high school/vocational school physics teachers. Data analysis techniques used are quantitative analysis techniques and qualitative analysis techniques. The instrument used to obtain perception data was categorized as valid with a value of Va = 3.11 and reliable with a Crobach's Alpha Coefficient calculated 0.925 greater than the standard Crobach's Alpha Coefficient value of 0.60. The results of the perception questionnaire analysis obtained an average percentage of teacher perceptions of 77.87% with a very good category.